INITIATIVES TO ENHANCE ELDERLY CARE COMPETENCIES THROUGH TRAINING FOR VOLUNTEERS VISITING SENIORS IN GAMPING, SLEMAN - Istichomah, Istichomah; Sri Handayani; Setyo Retno Wulandari; Firmina Theresia Kora (Sahabat Publikasi Kuu, 2025)
Introduction: The “Tirah Baring” Elderly-Friendly Visiting Volunteer Training is a joint program aimed at enhancing the quality of life for elderly individuals in the Special Region of Yogyakarta (DIY), namely in the Gamping District and adjacent areas. Bedridden or housebound elderly individuals are more susceptible to social isolation, health issues (such as pressure ulcers), and neglect, imposing a significant strain on family caregivers. This initiative aims to empower the local community by providing volunteer training, thereby equipping them to offer proficient and compassionate support. Methods: Outlines how the study was conducted, including the sample, data collection, and analysis methods. Results: Summarizes the key findings of the study, often referencing relevant tables or figures. Conclusion Serves to summarize the key fiddings and implication of the study, providing a concice overview of the research’s main takeaways. Keywords : training, volunteers, elderly